2005
DOI: 10.1116/1.2131875
|View full text |Cite
|
Sign up to set email alerts
|

Proton and anion distribution and line edge roughness of chemically amplified electron beam resist

Abstract: Nanoscale resist topography such as line edge roughness ͑LER͒ or line width roughness ͑LWR͒ is the most serious concern in sub-100 nm fabrication. Many factors have been reported to affect LER. However, the cause of LER is still unclear. We calculated proton and anion distribution of chemically amplified electron beam resists in order to make clear the cause of LER. Counter anion distribution is significantly different from proton distribution. Counter anions are inhomogeneously distributed outside a relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…In an attempt to solve this problem, the acid distribution in EB resists has been investigated, [30][31][32] and it was found that the resolution blur intrinsic to reaction mechanisms of chemically amplified EB resists degrades the image contrast of the initial acid distribution. 33,34) This finding suggested the consistency of image contrast theory with LER formation. 35) The reported factors that affect LER formation are summarized in Fig.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…In an attempt to solve this problem, the acid distribution in EB resists has been investigated, [30][31][32] and it was found that the resolution blur intrinsic to reaction mechanisms of chemically amplified EB resists degrades the image contrast of the initial acid distribution. 33,34) This finding suggested the consistency of image contrast theory with LER formation. 35) The reported factors that affect LER formation are summarized in Fig.…”
Section: Introductionsupporting
confidence: 66%
“…35) After the formation of the initial acid distribution as a boundary condition for diffusion, the LER of latent images is formed during acid-catalytic reactions accompanying acid diffusion. Because of the initial discrete distribution of acid molecules, 34,37) the roughness is initially decreased with acid diffusion by the smoothing effect of diffusion and is subsequently increased by the degradation of image contrast. 19,38,39) Therefore, all process and material factors associated with acid diffusion affect LER formation, as reported by many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…15 Among these factors, nonuniform distribution of resist components is one of the primary barriers to high resolution patterning of the resist materials. The heterogeneity in the materials has been related to polymer aggregation, 16,17 segregation of PAGs or other additives, 14,[18][19][20] or phase separation between protected and deprotected resists. 21 Although there have been many experimental studies and simulations to evaluate the heterogeneous distribution of resist components and its deleterious effects on the resolution of patterned structures as well as on LER, [16][17][18][19][20][21][22][23] the specific material structure-property relationships are not fully understood, and there have been no conclusions on how to control the size and distribution of the heterogeneities in the resist.…”
Section: Introductionmentioning
confidence: 99%
“…Although the acid production yield of the photoacid generator (PAG) of the chemically amplified resist had been studied 22,23) , the requirement of the EUV resist was still not satisfied yet. Thus, more effective fundamental work should require to be clarified the chemical reaction under EUV exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, more effective fundamental work should require to be clarified the chemical reaction under EUV exposure. The photo-ionization (ionization) reaction might be dominant and the secondary electron plays the important role in the chemical reaction under EUV exposure 23) . In addition, we had found out that the decomposition reaction was occurred near the large photo absorption atom in the solvent, so called "solvent effect" 24) .…”
Section: Introductionmentioning
confidence: 99%